Certain properties for analytic functions defined by a generalised derivative operator - Aisha Ahmed Amer,; Maslina Darus, (Penerbit Universiti Kebangsaan Malaysia, 2012)
In this paper, some important properties of analytic functions with negative coefficients defined by a generalised derivative operator are investigated. The properties include the necessary and sufficient conditions, radius of starlikeness, convexity and close-to-convexity.